Phenylpropanoids from the stems of Ephedra sinica. Issue 3 (3rd March 2016) - Zhang, Dan; Deng, An-Jun; Ma, Lin; Li, Zhi-Hong; Zhang, Zhi-Hui; Jiang, Jian-Dong; Qin, Hai-Lin
Abstract : Two new compounds of phenylpropanoids, ( S )- N -((1 R, 2 S )-1-hydroxy-1-phenylpropan-2-yl)-5-oxopyrrolidine-2-carboxamide (1 ) and (3 R )-3- O -β-d -glucopyranosyl-3-phenylpropanoic acid (2 ), were isolated from the stems of Ephedra sinica . Their structures were elucidated by in-depth examination of spectroscopic data, mainly including those from the 1D and 2D NMR and HRESIMS techniques, and chemical method. The absolute configurations of the two compounds were also corroborated through CD procedure.